Identifikasi Faktor yang Mempengaruhi Total Biaya Inventori Obat-obatan Golongan A di Rumah Sakit Swasta Tipe B di Jakarta Tahun 2015 - Agnes Susanto; Erna Kristin; Agastya Agastya (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
Inventory is one of the crucial components in hospital operations. The value o inventory may range up until 25% of the total cost of the hospital operation. Inventory optimization may save up to 10% in the minimum. There is a lot of drugs circulation in hospital. There is always a chance for a mistake. A tight control of inventory is necessary for hospital managers to minimize any potential waste. A saving directive for 20% drugs which consume 70% of the total cost will boost the hospital efficiency. A lot of factors influences hospital inventory and how managers strategize for the inventory. Some identified factors are order frequency, order quantity, unit price, and other hidden costs. The purpose of this research is to prove the correlation of each factor and how they influence the total inventory cost. To follow up the result, henceforth a model of simulation by calculating Economic Order Quantity and Reorder Point, the research may help hospital managers in modifying the strategy of managing hospital inventory for the next year period. This study aims to identify the factors which influence total inventory cost in managing group A drugs at private type B hospital, Jakarta. This study using observational analytics, cross-sectional study.